Adsorptive removal of fluoride from aqueous solution using single- and multi-walled carbon nanotubes - Dehghani, Mohammad Hadi; Haghighat, Gholam Ali; Yetilmezsoy, Kaan; McKay, Gordon; Heibati, Behzad; Tyagi, Inderjeet; Agarwal, Shilpi; Gupta, Vinod Kumar (ELSEVIER SCIENCE BV, 2016)
In the present study, defluoridation study of liquid phase with the help of multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs) were well investigated and elucidated. The impact of different experimental conditions such as solution pH, initial fluoride concentration, adsorbent dose, and contact time was well studied and optimized for the maximum fluoride removal from water. The experimental data were fitted by the Freundlich, Langmuir and Dubinin-Radushkevich (D-R) isotherm models and the related equilibrium constants were calculated. The results of the isotherm studies showed that fluoride removal by both adsorbents followed the Freundlich isotherm model. Kinetic studies were conducted and the results demonstrated that the experimental data were fitted well with the pseudo-second order kinetic model. Furthermore, two multiple regression-based equations were also derived to model the removal of fluoride from aqueous solutions by the carbon nanotubes. This study demonstrated that the polynomial equations satisfactorily described the behavior of the present defluoridation process for both MWCNTs (R-2 = 0.913) and SWCNTs (R-2 = 0.941). (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Fluorine removal; SWCNTs; MWCNTs; Modeling; BAGASSE FLY-ASH; ACTIVATED CARBON; WASTE-WATER; METHYL-ORANGE; TITANIUM-DIOXIDE; SUGAR-INDUSTRY; GRAPHENE OXIDE; BASIC DYE; SORPTION; PHASE; Chemistry; Physics